Lyssavirus surveillance in fruit bats at a livestock breeding centre in Perak, Malaysia - Mikail, Muhammed (2018)
Fruit bats of the family Pteropodiformes constituted about 21 species out of 110 species of bats found in Peninsular Malaysia. These bats are known to be potential reservoirs of emerging viral zoonosis such as the Lyssavirus, Nipah virus, Tioman virus and Palau virus. Malaysian Fruit bats are threatened with habitat loss due to conversion of forest into agricultural and urban areas which subsequently result to encroachment of fruit bats into other habitat such as livestock and agricultural farms for foraging, roosting or both, hence these farms are at risk of spill over infection from wildlife due to close proximity or contact with contaminated discard fruit with other livestock or humans. All the 14 recognized Lyssaviruses with the exception of Mokola lyssavirus are known to spill over from bats to susceptible wildlife, livestock or pets and humans. The rabies lyssavirus reservoir host status of Malaysian fruit bats or any other Malaysian wildlife mammals is not known, hence the spill over risk is also not known and until 2015, when Malaysia lost its rabies free status, dogs are known to be the only reservoir host of rabies lyssavirus and responsible for rabies outbreak in Malaysia. The occurrence and transmission of bat lyssaviruses depends on several factors such as the host, host ecology, host species distribution and the particular population under study. The aim of this study is to determine the possibilities of fruit bats encroaching livestock farms that borders wildlife sanctuaries, the fruit bats species diversity in a livestock farm for possible risk of spill over infection and determine the possibility of Malaysian fruit bats, as rabies lyssavirus reservoirs host. Fifty individual fruit bats (50) were captured in a livestock area, identified to species level, and brain tissues were collected for histopathology. Cynopterus brachyotis was the highest captured fruit bat species, representing 40% of the total capture. The findings of Shannon index is 2.80 and Simpson index is 0.2 are suggestive of a degree of species dominance with low diversity in Lenggong livestock breeding centre. There was no report or published study about demonstration of pathognomonic Negri bodies for rabies lyssavirus in its wildlife reservoir host in Malaysian mammals such as the bats; hence a gap exists in the knowledge of the Lyssavirus reservoir host status of Malaysian fruit bats. This study, Following H & E staining, demonstrated perivascular cellular infiltrates in five (5) brain tissues of fruit bats (Cynopterus brachyotis) which is suggestive of viral infection and the pathognomonic rabies Negri bodies in one of the fruit bats brain tissue (Cynopterus brachyotis), which are suggestive of rabies lyssavirus. This study suggests that fruit bats are indeed; encroaching livestock farm that borders wildlife sanctuary, the species diversity was low and could be potential source of infection to susceptible livestock and bat rabies lyssavirus could exists in Malaysian fruit bats.